A legitimação político-pública do direito segundo a teoria discursiva de Jürgen Habermas - Aidar, Adriana Marques (2009)
Using the book Direito e Democracia entre facticidade e validade as a theoretical landmark, the author intends to present, in this dissertation, that the reconstruction of the role of law is crucial in how the philosopher proposes the structure and legitimacy of the democratic Rule of law. Habermas seeks to interpret the society from a vision of the internal legal system and using the theory of communicative action makes possible the realization of the criticism of formal democracy and enables the investigation of the validity of a plea of legitimate order. He abandons the form that the relationship between law and moral had in his theory, separates the two spheres and denies the relation of hierarchy and subordination of the law in relation to moral, which until then was held in his work. Changing the way he sees the role of law (which becomes the medium for social integration of modern communities), Habermas also needs to change his proposals on how it verifies and certifies the legitimacy of law, because by then the answer was in moral itself, as a last resort to which recourse. With the statement that law and moral spheres are complementary and co-originating, the philosopher presents a legitimate process that draws its strength from the intersubjective understanding of those who act communicative, through the acceptance of claims of validity. To receive the burden of social integration, the law is in the responsibility to institutionalize the results of the discursive formation of opinion and the will of the subject. The democratic process is responsible for the institutionalization of the interests of all subjects. On the moral sphere subjects guide themselves only to defend of their private freedoms. It will be seen also that for Habermas, private autonomy and public autonomy should also be seen as co-originating, it means that to the Rule of law needs be sustained, there should not be a relationship of prevalence of a form of autonomy on the other. The legitimacy of a law depends on the balance private autonomy and public autonomy of citizens. The conflict between the scope of autonomy should be resolved by reference to what the philosopher calls "common ground" to both, which is the discourse, and a intersubjective knowledge of an system of rights composed of fundamental rights. The light of this idea does not exists in discourse picked by the chance. It exists in the principle discursive, its specification in the universalizing principle and the principle of democracy. There will be also the relationship between political power and communicative power that gives the opportunity to tie all the elements shown in the statement that citizens may be considered co-authors of the standards (which are subject to the condition of subjects on their private life) if the law that is legitimate for them, in exercise of their political autonomy, being responsible for the direction of political power.